9 Imaging in hereditary haemochromatosis: establishing a local guideline for cardiac and hepatic surveillance. (October 2018) - Traynor, BP; Hazel, K; O'Donnell, J; Farrell, RJ; Smyth, C; Kelly, O
Abstract : Introduction: Hereditary haemochromatosis (HH) is an autosomal recessive condition, most commonly caused by HFE gene mutations. The prevalence of HH in Ireland is 1 in 83 per head of population. Untreated HH may lead to cirrhosis, hepatocellular carcinoma (HCC), diabetes and non-dilated cardiomyopathy. Hepatic and myocardial iron deposition can be reproducibly quantified using T2* MRI. Echocardiography can identify early pathophysiology due to iron overload. Iron overload cardiomyopathy can be effectively managed with conventional heart failure treatment along with venesection or iron chelation. Aim: There are no definitive guidelines in HH for the frequency of liver or cardiac imaging to assess for complications of iron overload. Our aim was to assess our patient cohort in order to establish a local guideline for interval surveillance. Methods: Data were collated for those attending for venesection at Connolly Hospital. Our laboratory system was used to attain genotype, ferritin at diagnosis and liver function tests. NIMIS was used to determine if patients had undergone liver or cardiac imaging. Chi-squared analyses were employed to evaluate a correlation between ferritin at diagnosis and evidence of hepatic or cardiac dysfunction. Results: 279 patients were included, 80 female and 199 male with a median age of 52 years. 264 ferritin results were recorded. 155 patients had ferritin levels over 500 at diagnosis and 109 less than 500. Of the ferritin <500 group, 70 underwent liver imaging, 32 having normal and 38 having abnormal results. In the ferritin >500 cohort, 105 underwent liver imaging, with 34 normal and 71 abnormal results. Ferritin >500 at diagnosis is not indicative of end stage liver dysfunction (p=0.08). Ferritin >500 at diagnosis is associated with abnormal liver imaging, most commonly hepatosteatosis. Four patients had radiological signs consistent with cirrhosis (p=ns). No patients were diagnosed with HCC. 42 patients had undergone echocardiography. 19 had structural abnormalities, while 23 had normal studies. Left ventricular diastolic dysfunction was reported in 17 of the 19 abnormal studies. Ferritin >500 showed a statistically insignificant correlation with cardiac structural abnormality (p=ns), likely due to low patient numbers with imaging. Males were more likely to undergo echocardiography Conclusion: Ferritin level >500 at diagnosis is not associated with an increased risk for liver dysfunction and, therefore, interval for liver screening may be decreased to 18-monthly, yielding cost savings. Although numbers are small, there appears to be a correlation between high ferritin levels and cardiac structural abnormality. Therefore, we recommend that all patients undergo echocardiography at diagnosis and every 1–2 years thereafter. Patients who demonstrate abnormalities on echocardiography should be referred to specialist cardiac services and undergo cardiac MRI with T2* imaging.